2014
DOI: 10.3109/01676830.2014.902478
|View full text |Cite
|
Sign up to set email alerts
|

Series of Extranodal Natural Killer/T-cell Lymphoma, Nasal Type, with Periorbital Involvement

Abstract: Extranodal natural killer/T-cell lymphoma, nasal type, should be suspected in a painless periorbital cellulitis with chronic sinusitis, not responding to conventional therapy. A high index of suspicion is necessary in biopsies showing angiodestruction and necrosis. Epstein-Barr virus encoded RNA in situ hybridization and expert hematopathologist consultation is necessary to decrease the delay in diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 27 publications
3
25
0
2
Order By: Relevance
“…Very few cases with periorbital cellulitis as the initial presentation of NKTCL have been reported in the literature, as we report in our case [810]. Termote et al described 3 similar cases, all treated by chemo-radiotherapy, but they died within 5–35 months of diagnosis [8]. The other similar presentation was described by Kim JW et al and was treated as sinusitis, but biopsies taken after relapses confirmed NKTCL diagnosis [9].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Very few cases with periorbital cellulitis as the initial presentation of NKTCL have been reported in the literature, as we report in our case [810]. Termote et al described 3 similar cases, all treated by chemo-radiotherapy, but they died within 5–35 months of diagnosis [8]. The other similar presentation was described by Kim JW et al and was treated as sinusitis, but biopsies taken after relapses confirmed NKTCL diagnosis [9].…”
Section: Discussionsupporting
confidence: 75%
“…Clinically, it can be divided into nasal and extranasal types [4]; the nasal variety commonly presents with nasal obstruction, but also it can cause epistaxis, extensive involvement of the midfacial structure, involvement of the orbit causing proptosis, and, occasionally, the hard palate [4,5,7]. Very few cases with periorbital cellulitis as the initial presentation of NKTCL have been reported in the literature, as we report in our case [810]. Termote et al described 3 similar cases, all treated by chemo-radiotherapy, but they died within 5–35 months of diagnosis [8].…”
Section: Discussionmentioning
confidence: 69%
“…It was only after repeated recurrences and multiple biopsies that a diagnosis of NKTL involving the lacrimal sac, orbit and the nasal cavity was made. Termote et al 19 reported a case series comprising three patients with periorbital involvement from NKTL who all developed painless eyelid swelling, which, along with a history of chronic sinusitis with nasal congestion, masqueraded as periorbital cellulitis. The diagnosis was established from biopsies of the orbital mass, and in one case of the cervical lymphadenopathy 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Cases could present with painless periorbital cellulitis with chronic sinusitis. 59 Only 8 cases of isolated orbital involvement without nasal mucosal involvement have been reported in the literature. Majority of the patients were middle-aged males.…”
Section: Natural Killer/t-cell Lymphomamentioning
confidence: 99%
“…Epstein-Barr virusencoded RNA in situ hybridization would assist in diagnosing the disease. 59 Natural killer/T-cell lymphoma involving the orbit typically runs an aggressive course. In the largest series reported by Woog et al, 60 6 of 8 patients died within 1 year after presentation, and the 5-year mortality rate was up to 87.5% despite radiation and/or chemotherapy.…”
Section: Natural Killer/t-cell Lymphomamentioning
confidence: 99%